Population‐neuroscience study of the Tokyo TEEN Cohort (pn‐TTC): Cohort longitudinal study to explore the neurobiological substrates of adolescent psychological and behavioral development. Issue 5 (19th February 2019) - Okada, Naohiro; Ando, Shuntaro; Sanada, Motoyuki; Hirata‐Mogi, Sachiko; Iijima, Yudai; Sugiyama, Hiroshi; Shirakawa, Toru; Yamagishi, Mika; Kanehara, Akiko; Morita, Masaya; Yagi, Tomoko; Hayashi, Noriyuki; et al.
Abstract : Aim: Adolescence is a crucial stage of psychological development and is critically vulnerable to the onset of psychopathology. Our understanding of how the maturation of endocrine, epigenetics, and brain circuit may underlie psychological development in adolescence, however, has not been integrated. Here, we introduce our research project, the population‐neuroscience study of the Tokyo TEEN Cohort (pn‐TTC), a longitudinal study to explore the neurobiological substrates of development during adolescence. Methods: Participants in the first wave of the pn‐TTC (pn‐TTC‐1) study were recruited from those of the TTC study, a large‐scale epidemiological survey in which 3171 parent–adolescent pairs were recruited from the general population. Participants underwent psychological, cognitive, sociological, and physical assessment. Moreover, adolescents and their parents underwent magnetic resonance imaging (MRI; structural MRI, resting‐state functional MRI, and magnetic resonance spectroscopy), and adolescents provided saliva samples for hormone analysis and for DNA analysis including epigenetics. Furthermore, the second wave (pn‐TTC‐2) followed similar methods as in the first wave. Results: A total of 301 parent–adolescent pairs participated in the pn‐TTC‐1 study. Moreover, 281 adolescents participated in the pn‐TTC‐2 study, 238 of whom were recruited from the pn‐TTC‐1 sample. The instruction for data request is available at: http://value.umin.jp/data‐resource.html . Conclusion: The pn‐TTC project is a large‐scale and population‐neuroscience‐based survey with a plan of longitudinal biennial follow up. Through this approach we seek to elucidate adolescent developmental mechanisms according to biopsychosocial models. This current biomarker research project, using minimally biased samples recruited from the general population, has the potential to expand the new research field of population neuroscience.